Управление освещением в системе «умный дом» - Блинов, Б. Ю.; Сайківська, Л. Ф. (ХНУРЕ, 2018)
This article discusses the home lighting control system. The list lists the main functions of the system. The components of this system are described. The main advantages of the control system are listed. The principles of the lighting system operation are also considered depending on the device used.
Keywords: управление освещением; умный дом; датчик освещенности